Serum calprotectin as new biomarker for disease severity in idiopathic pulmonary fibrosis: a cross-sectional study in two independent cohorts. Issue 1 (15th January 2021) - Machahua, Carlos; Guler, Sabina A.; Horn, Michael P.; Planas-Cerezales, Lurdes; Montes-Worboys, Ana; Geiser, Thomas K.; Molina-Molina, Maria; Funke-Chambour, Manuela
Abstract : Background: Non-invasive biomarkers for the assessment of disease severity in idiopathic pulmonary fibrosis (IPF) are urgently needed. Calprotectin belongs to the S-100 proteins produced by neutrophils, which likely contribute to IPF pathogenesis. Calprotectin is a well-established biomarker in inflammatory bowel diseases. In this cross-sectional study, we aimed to establish the potential role of calprotectin as a biomarker in IPF. Specifically, we hypothesised that patients with IPF have higher serum calprotectin levels compared with healthy controls, and that calprotectin levels are associated with disease severity. Methods: Blood samples were obtained from healthy volunteers (n=26) and from two independent IPF cohorts (derivation cohort n=26, validation cohort n=66). Serum calprotectin levels were measured with a commercial kit adapted for that purpose and compared between healthy controls and patients with IPF. Clinical parameters, including forced vital capacity, diffusing capacity for carbon monoxide (DLCO) and the Composite Physiologic Index (CPI), were correlated with calprotectin serum levels. Results: The IPF derivation cohort showed increased serum calprotectin levels compared with healthy controls (2.47±1.67 vs 0.97±0.53 µg/mL, p<0.001). In addition, serum calprotectin levels correlated with DLCO% predicted (r=−0.53, p=0.007) and with CPI (r=0.66, p=0.007). These findings were confirmed in an independent IPF validation cohort. Conclusion: Serum calprotectin levels are significantly increased in patients with IPF compared with healthy controls and correlate with DLCO and CPI. Calprotectin might be a potential new biomarker for disease severity in IPF.